Coronavirus disease 2019-associated coronary endotheliitis and thrombotic microangiopathy causing cardiogenic shock: a case report. Issue 2 (17th February 2022) - Valiton, Valérian; Bendjelid, Karim; Pache, Jean-Claude; Roffi, Marco; Meyer, Philippe
Abstract: Background: Coronavirus disease 2019 (COVID-19) primarily affects the respiratory tract but serious cardiovascular complications have been reported. Up to one-third of patients admitted to the intensive care unit may develop an acute myocardial injury, characterized by cardiac troponin elevation. However, the pathology underlying COVID-19-associated myocardial injury has rarely been reported. Case summary: Three days after being diagnosed for a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, a 52-year-old woman without a notable past medical history developed cardiogenic shock with severely reduced left ventricular ejection fraction (LVEF) at 25%. Coronary angiography was normal. Endomyocardial biopsy demonstrated coronary endotheliitis with multiple microvascular thromboses but no lymphocytic infiltrate and a negative polymerase chain reaction for SARS-CoV-2. The patient was implanted with a short-term LV assist device (Impella CP ®, Abiomed, Aachen, Germany) and treated with therapeutic anticoagulation. She suffered from concomitant respiratory failure that required 14 days of orotracheal intubation, 10 days of dexamethasone, and broad-spectrum antibiotics. Clinical outcome was favourable with weaning of the Impella device after 6 days and full recovery of LVEF (65%) at 30 days. Cardiac magnetic resonance performed at Day 30 showed no evidence of myocarditis or scars and confirmed the normalization of LVEF. Discussion: This case highlights how COVID-19-associated coronary endotheliitis and thrombotic microangiopathy, in the absence of myocarditis, may induce transient severe LV dysfunction and cardiogenic shock.